2022
DOI: 10.1038/s41398-022-02282-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in schizophrenia patients with a history and presence of auditory verbal hallucination

Abstract: Although many studies have demonstrated structural brain abnormalities associated with auditory verbal hallucinations (AVH) in schizophrenia, the results remain inconsistent because of the small sample sizes and the reliability of clinical interviews. We compared brain morphometries in 204 participants, including 58 schizophrenia patients with a history of AVH (AVH + ), 29 without a history of AVH (AVH−), and 117 healthy controls (HCs) based on a detailed inspection of medical records. We further divided the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…These findings indicate a reduced left-hemisphere lateralisation for language perception, which has been associated with greater AVH severity (Hugdahl et al, 2012), mediated by impaired functional and structural interhemispheric auditory connectivity (Steinmann et al, 2019). Such AVH severity, in turn, has been linked to asymmetric structural abnormalities, including reduced grey matter volume in the left insula (Romeo and Spironelli, 2022), and a smaller surface area in this area of the brain in actively hallucinating schizophrenia participants compared to healthy controls (Sone et al, 2022).…”
Section: Using Pavlovian Conditioning To Explore Left Lateralisation ...mentioning
confidence: 90%
“…These findings indicate a reduced left-hemisphere lateralisation for language perception, which has been associated with greater AVH severity (Hugdahl et al, 2012), mediated by impaired functional and structural interhemispheric auditory connectivity (Steinmann et al, 2019). Such AVH severity, in turn, has been linked to asymmetric structural abnormalities, including reduced grey matter volume in the left insula (Romeo and Spironelli, 2022), and a smaller surface area in this area of the brain in actively hallucinating schizophrenia participants compared to healthy controls (Sone et al, 2022).…”
Section: Using Pavlovian Conditioning To Explore Left Lateralisation ...mentioning
confidence: 90%
“…In cases of deafness or compromise of the pontine inhibitory pathways over these musical memory circuits, anomalous disinhibition of these circuits and liberation of this type of memory in the form of musical auditory hallucinations may occur 4 . A recent report suggested that patients with schizophrenia who exhibited verbal auditory hallucinations had significantly smaller bilateral hippocampal volumes and smaller surface areas in the left superior frontal cortex and caudal middle frontal gyrus 5 . While functional changes in the occipital lobe have been noted in DLB, atrophy of the medial temporal lobe, especially the hippocampus, has been observed in some cases 6 .…”
Section: Figurementioning
confidence: 99%
“…4 A recent report suggested that patients with schizophrenia who exhibited verbal auditory hallucinations had significantly smaller bilateral hippocampal volumes and smaller surface areas in the left superior frontal cortex and caudal middle frontal gyrus. 5 While functional changes in the occipital lobe have been noted in DLB, atrophy of the medial temporal lobe, especially the hippocampus, has been observed in some cases. 6 A previous study showed that in patients with DLB and visual hallucinations, there were significant decreases in the left inferior parietal lobule, left superior temporal gyrus, and right primary visual cortex, while with auditory hallucinations, there were significant increases in the right middle occipital and right inferior occipital gyri as observed by brain perfusion single-photon emission computed tomography.…”
mentioning
confidence: 99%
“…On a morphological level, post-mortem studies in humans provide evidence for cytoarchitectonic asymmetries (Galaburda, Sanides, and Geschwind 1978) and macroscopic asymmetries such as the ‘Yakovlevian-Torque’ can be observed by pure visual inspection. From the clinical perspective, there is emerging evidence for the association of altered or disrupted hemispheric asymmetry in neurological disorders and neuropsychological conditions (Postema et al 2019; Sone et al 2022; Lubben et al 2021).…”
Section: Introductionmentioning
confidence: 99%